2021
DOI: 10.3847/2041-8213/ac2513
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Ionized Calcium in the Atmosphere of the Ultra-hot Jupiter WASP-76b

Abstract: Recent observations of the ultra-hot Jupiter WASP-76b have revealed a diversity of atmospheric species. Here we present new high-resolution transit spectroscopy of WASP-76b with GRACES at the Gemini North Observatory, serving as a baseline for the Large and Long Program “Exploring the Diversity of Exoplanet Atmospheres at High Spectral Resolution” (Exoplanets with Gemini Spectroscopy, or ExoGemS for short). With a broad spectral range of 400–1050 nm, these observations allow us to search for a suite of atomic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 54 publications
10
39
0
Order By: Relevance
“…The weight-combined results are shown in dark-blue, together with the unweighted results (light-blue) and literature values using the same HARPS/HARPS-N data (grey). The salmon-coloured points show recent results from other high-resolution spectrographs: WASP-69b with CARMENES (Khalafinejad et al 2021), WASP-76b with ESPRESSO (Tabernero et al 2021) and GRACES (Deibert et al 2021), and WASP-121b with ESPRESSO (Borsa et al 2021). We find that ℎ Na is well-described by an exponential trend of the form…”
Section: Relative Height Of the Sodium D2 Linesupporting
confidence: 74%
See 1 more Smart Citation
“…The weight-combined results are shown in dark-blue, together with the unweighted results (light-blue) and literature values using the same HARPS/HARPS-N data (grey). The salmon-coloured points show recent results from other high-resolution spectrographs: WASP-69b with CARMENES (Khalafinejad et al 2021), WASP-76b with ESPRESSO (Tabernero et al 2021) and GRACES (Deibert et al 2021), and WASP-121b with ESPRESSO (Borsa et al 2021). We find that ℎ Na is well-described by an exponential trend of the form…”
Section: Relative Height Of the Sodium D2 Linesupporting
confidence: 74%
“…The relative height, ℎ Na , is calculated using the measured sodium D2 line depths for the weight-combined spectra (dark-blue), unweighted spectra (light-blue), literature values using the same HARPS/HARPS-N data (grey), and literature values using other high-resolution spectrographs (salmon). References for results from other instruments: WASP-69b with CARMENES(Khalafinejad et al 2021), WASP-76b with ESPRESSO(Tabernero et al 2021) and GRACES(Deibert et al 2021), and WASP-121b with ESPRESSO(Borsa et al 2021). The exponential curve described by equation 15 is shown in orange and was fitted to the weight-combined results.…”
mentioning
confidence: 99%
“…This assumption is true for a majority of the atmosphere modeled, except for perhaps near the top boundary of our model. Deibert et al (2021) found their NLTE model to be a slightly better fit than their LTE model of WASP-76b, but both models significantly underestimated the line depths. Its important to note how-Figure 8.…”
Section: Discussionmentioning
confidence: 86%
“…Our models are all based on parameters from the UHJ WASP-76b, an inflated planet orbiting its host star every 1.81 days. This planet has been the target of many high-resolution transit analyses, and a multitude of different species have been detected in its atmosphere, including Fe I, Na, Li I, Ca II (Seidel et al 2019;Deibert et al 2021;Casasayas-Barris et al 2021;Kawauchi et al 2021;Tabernero et al 2021), and recently molecules like OH (Landman et al 2021).Analyses of high resolution emission spectra have yet to be published. The work by Kesseli et al (2021) explores an entire atomic spectral survey of the atoms and ions that have been detected on this UHJ and finds evidence for temperature and chemical gradients on the planet.…”
Section: Introductionmentioning
confidence: 99%
“…For example, many species have been detected via high-resolution transmission spectroscopy in the hottest known exoplanet -KELT-9b, including hydrogen Balmer lines, Fe i, Fe ii, Ti ii, Ca ii, Mg i, and O i (Yan & Henning 2018;Hoeijmakers et al 2018Hoeijmakers et al , 2019Yan et al 2019;Cauley et al 2019;Turner et al 2020;Wyttenbach et al 2020;Borsa et al 2021b;Pai Asnodkar et al 2022). Various chemical species have also been discovered in other UHJs such as KELT-20b/MASCARA-2b (Casasayas-Barris et al 2018Stangret et al 2020;Hoeijmakers et al 2020a;Rainer et al 2021), WASP-76b (Seidel et al 2019;Žák et al 2019;Ehrenreich et al 2020;Tabernero et al 2021;Casasayas-Barris et al 2021;Deibert et al 2021;Landman et al 2021;Kesseli et al 2022), WASP-121b (Sing et al 2019;Bourrier et al 2020;Cabot et al 2020;Ben-Yami et al 2020;Hoeijmakers et al 2020b;Borsa et al 2021a), TOI-1518b (Cabot et al 2021), and HAT-P-70b (Bello-Arufe et al 2022).…”
Section: Introductionmentioning
confidence: 99%